Use of conversation theory to underpin blended learning. (26th June 2007) - Heinze, Aleksej; Procter, Chris; Scott, Bernard
Our work is concerned with the search for a viable pedagogical theory for a part time information technology course facilitated in blended learning. It was initially thought that the Conversational Framework (Laurillard, 1993) would provide this, and could be examined utilising action research. We examine the Conversation Theory related literature (Scott, 2001; Harri-Augstein and Thomas, 1991) and our action research data, including staff and student interviews and focus groups. The findings suggest that despite some theoretical alignment with Blended Learning, there is a need to amend and enrich the Conversational Framework in order to make it more applicable.